The Arabidopsis LYSIN MOTIF-CONTAINING RECEPTOR-LIKE KINASE3 Regulates the Cross Talk between Immunity and Abscisic Acid Responses . Issue 1 (17th March 2014) - Paparella, Chiara; Savatin, Daniel Valentin; Marti, Lucia; De Lorenzo, Giulia; Ferrari, Simone
Abstract : An Arabidopsis receptor-like kinase negatively regulates defense gene expression and resistance against microbial pathogens and is required for late responses to abscisic acid . Abstract: Transmembrane receptor-like kinases characterized by the presence of one or more lysin motif (LysM) domains in the extracytoplasmic portion (LysM-containing receptor-like kinases [LYKs]) mediate recognition of symbiotic and pathogenic microorganisms in plants. The Arabidopsis ( Arabidopsis thaliana ) genome encodes five putative LYKs; among them, AtLYK1/CHITIN ELICITOR RECEPTOR KINASE1 is required for response to chitin and peptidoglycan, and AtLYK4 contributes to chitin perception. More recently, AtLYK3 has been shown to be required for full repression, mediated by Nod factors, of Arabidopsis innate immune responses. In this work, we show that AtLYK3 also negatively regulates basal expression of defense genes and resistance to Botrytis cinerea and Pectobacterium carotovorum infection. Enhanced resistance of atlyk3 mutants requires PHYTOALEXIN-DEFICIENT3, which is crucial for camalexin biosynthesis. The expression of AtLYK3 is strongly repressed by elicitors and fungal infection and is induced by the hormone abscisic acid (ABA ), which has a negative impact on resistance against B. cinerea and P. carotovorum . Plants lacking a functional AtLYK3 also show reduced physiological responses to ABA and are partially resistant to ABA -induced inhibition of PHYTOALEXIN-DEFICIENT3 expression. These results indicate that AtLYK3 is important for the cross talk between signaling pathways activated by ABA and pathogens.